Inspired people produce results : how great leaders use passion, purpose, and principles to unlock incredible growth - Kingsley, Jeremy (McGraw-Hill, 2013)
Revealing the essential principles and skills for effective leadership in the twenty-first century; this fast-paced; enjoyable book provides the tools; the skills; and the inspiration you need to lead your people and your organization to greatness. --